Nucleotide sequence analysis of endogenous murine leukemia virus-related proviral clones reveals primer-binding sites for glutamine tRNA. - Nikbakht, K N (1985)
Nucleotide sequences of the region that corresponds to the site of tRNA primer binding for a functional retrovirus were determined in five murine leukemia virus-related sequence clones from mouse chromosomal DNA, which contain a unique 170 to 200-base-pair additional internal segment in the long terminal repeats. The 3'-terminal 18-nucleotide sequence of a major glutamine tRNA isoacceptor was found to match well with the putative primer binding site: 18 of 18 in three clones, 17 of 18 in one clone, and 16 of 18 in one clone. This implies that most of these endogenous proviral sequences of the mouse genome, if replicated as retroviruses, will be different from ecotropic murine leukemia viruses and most mammalian type C retroviruses in using glutamine tRNA, rather than proline tRNA, as a primer.